Grundtvig som kontextuell teolog - Holmberg, Anders (Grundtvig-studier, 1996)
Grundtvig as a Contextual Theologian By Anders HolmbergA comparison between Swedish and Danish theology and church life makes it clear that Grundtvig has affected Denmark in a way that has no immediate parallel in Sweden. The point of departure for Holmberg’s study is the assumption that this is due to the unique concord between Grundtvig’s theology and the Danish society in the 19th century. This concord is illustrated by the inclusion of the concept of »contextual theology« which has played an importantrole in the Swedish theological scholarship of recent years, owing to the Anglo-Saxon influence on Swedish theology. The concept of contextual theology is explained on the basis of the American theologian Stephen B. Bevans’s discussion of the concept. With this approach Holmberg wants to throw light on Grundtvig’s theological method rather than his final result. Thus, the goal is to be able to answer the question whether Grundtvig’s theology can be described as a contextual theology. For this purpose, one of Grundtvig’s principal works, Den christelige B.rnel.rdom (Elemental Christian Teaching) is used.In his account of contextual theology Bevans distinguishes between five different methods, all of them serving to illuminate the relationship between Christian faith and the surrounding contemporary culture. The terms he uses for these methods are 1) the translation model, 2) the anthropological model, 3) the practise model, 4) the synthesis model, and 5) the transcendental model.Holmberg believes that elements of Grundtvig’s theology can be elucidated on the basis of all five methods, but concludes that especially the anthropological and the transcendental models harmonize with Grundtvig’s theology.The anthropological model assumes that the revelation of God takes place spontaneously in culture. It is not possible to distinguish between the Christian identity and culture since faith finds its true expression in man’s own language and culture. This is reminiscent of Grundtvig’s ideas about Christianity and folk culture, even though, with his emphasis on the Apostolic Creed as the foundation of Christianity, Grundtvig defines the identity of the Christian faith with greater precision than is the case with the anthropological model. Compared with that model, Grundtvig is also more firmly attached to the Christian tradition than to contemporary culture. The fact that Danish culture was completely saturated with Christian faith at the time of Grundtvig finds expression in his ideas about the interaction of Christianity and folk culture. This is in keeping with the anthropological model.The transcendental model operates with an individual believer as its starting- point, since it explains how this individual’s religious experience is expressed authentically through actual cultural conditions. In continuation of Svend Bjerg’s research, Holmberg maintains that Grundtvig’s theology is based precisely on the experiences of his own life, and that consequently his theology has since been able to lead to similar life experiences.On the background of his analyses Holmberg concludes that it is possible to regard Grundtvig as a contextual theologian. Continuing this line of thought, he points out that it is difficult in our time to make direct use of Grundtvig’s theological thinking in an attempt to formulate the Christian faith in a present-day Nordic context. It is, however, quite possible to learn from Grundtvig’s working method.